Quality Study of Public Open Spaces in Bandung City Parks Based on Responsive Environment (Case Study of Cisangkuy Elderly Park) - Subagja, Pridiaz (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2023)
Public open spaces in urban areas consist of green and non-green open spaces, both of which play an important role in social, ecological, and economic balance for the community. City parks, which are one type of green open space, are a necessary facility in a region or city, one of which is the city of Bandung. Parks in Bandung are a vital element of public space that supports social and recreational activities for residents. However, during the Covid-19 pandemic in 2020, this phenomenon presented a contrasting situation. On the one hand, public open spaces became a popular place for people to gather because they were not allowed to stay indoors with many people for long periods of time. However, when lockdown measures were imposed, there was a decline in the function of parks, which also led to a decline in their quality. This impact was exacerbated by rampant theft, which caused damage and vandalism to park facilities. The government has made efforts to repair and maintain city parks, one of which is the renovation of parks and the provision of facilities, such as the Elderly Park, which is the case study of this research. This study aims to identify the quality of public open spaces using the case study of the Elderly Park, which can be examined from the concept of a responsive environment. This study uses a descriptive-qualitative method, beginning with data collection through direct field observations as a basis for identifying the quality of public open spaces. results showed the identification of park quality based on seven indicators, namely permeability, variety, legibility, robustness, visual appropriateness, richness, and personalization. This study is useful as an indicator of public open space quality that can attract and encourage the surrounding community and government to plan adaptive public open space revitalization, especially after the pandemic.